Penerapan Aplikasi Arteri untuk Kegiatan Alih Media Arsip di Kantor Dinas Perpustakaan dan Kearsipan Kota Sungai Penuh - Kurniadi, Gian; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
abstractThis paper discusses the application of applications for media transfer activities at Kantor Dina Perpustakaan dan Kearsipan Kota Sungai Penuh. The objectives of writing this paper are: (1) to find out how to apply Arterial archive applications, (2) to find out the constraints faced, (3) and find out the efforts made by Kantor Dinas Perpustakaan dan Kearsipan in overcoming obstacles . The research method used is descriptive method, where the author describes the facts that occur during research activities. First, in the field of archives, archivists are required to be able to obtain information easily, quickly, precisely and accurately and to maintain and maintain the physical condition of the archive to be safe and not easily damaged. The application of the Arterial archive application can assist in answering the demands given to the archivists. The stages in the application of Arterial archive applications include: the preparation, installation, and operation stages. Second, the obstacles faced in implementing applications such as lack of archivist competence in the field of technology, especially computers, facilities and infrastructure that are less supportive in the application of electronic archive applications such as the unavailability of a scan engine for archival media transfer activities. Third, several efforts were made such as: increasing archivist competence by attending trainings. To fulfill all the equipment needed in the application of the archive application, the loan is first made up to the procurement of equipment.Keyword:Â media transfer, archive, arteri.